2012
DOI: 10.1186/2192-2853-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the factors affecting co-localization precision for quantitative multicolor localization microscopy

Abstract: This work explores the potential of multi-color Photoactivated Localization Microscopy (PALM) imaging to probe sub-diffraction limit interactions between proteins with spectrally separated labels. Using a PALM setup built around a commercial microscope axially stabilized to nm-level, we determined the ultimate registration accuracy that could be achieved (10 nm) and compared the performance of three different pairs of fluorescent proteins that can be used in dual color PALM. Fusion constructs were cloned and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 40 publications
0
65
0
Order By: Relevance
“…As shown in previous studies, blinking of PAFPs can be corrected by combining fluorescent bursts from a single molecule based on a cutoff time determined from the measured characteristic darktime distribution (25,27). In addition, it has been previously reported that the detectable fraction of PAFPs can be substantially smaller than 100% (29)(30)(31). Both the blink characteristics and the detectable fraction are sensitive to the experimental conditions.…”
Section: Calibration Of Single-molecule Superresolution Microscopy Elmentioning
confidence: 97%
“…As shown in previous studies, blinking of PAFPs can be corrected by combining fluorescent bursts from a single molecule based on a cutoff time determined from the measured characteristic darktime distribution (25,27). In addition, it has been previously reported that the detectable fraction of PAFPs can be substantially smaller than 100% (29)(30)(31). Both the blink characteristics and the detectable fraction are sensitive to the experimental conditions.…”
Section: Calibration Of Single-molecule Superresolution Microscopy Elmentioning
confidence: 97%
“…In the case of PA-FPs, the fraction is even lower, due to incomplete photo-conversion. In the case of the relatively bright PA-FP mEOS2, this fraction is about 60%, and for several other PA-FPs it can be as low as 40% [25,49]. This can directly affect counting studies, as the number of counted molecules can be underestimated by the same fraction (Fig.…”
Section: Detection Efficiencymentioning
confidence: 99%
“…Other quantification measures might also be affectedfor example, in the case of SM co-localization, assuming that the used co-localization measure is linearly related to the detection efficiency, the co-localization will be underestimated by a fraction xy, where x is the detection efficiency in one channel, and y in the other, leading to an underestimate of as low as 20% for commonly used PA-FP pairs (Fig. 4c) [49]. However, in practice, the effect of limited detection efficiency on cluster (Fig.…”
Section: Detection Efficiencymentioning
confidence: 99%
See 2 more Smart Citations